El papel de las humanidades en la formación profesional en Colombia (2021)
This reflection article presents various aspects of humanities seen from different perspectives. The objective of this article is to reflect about the spaces of the humanities areas in higher education, in order to train people with integrity and professional ethics. The article details the theoretical and conceptual aspects of humanities. It also offers a proposal for the strengthening of human competence seen from various perspectives (family, society, education, nature, art and professions). Finally, it develops some conclusions considering that the humanities must be applied in any context, not only the academic one, but also the social one.